2021
DOI: 10.3389/fpsyg.2021.596278
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an In-vehicle Collision Warning System on Older Drivers' On-road Head Movements at Intersections

Abstract: With age might come a decline in crucial driving skills. The effect of a collision warning system (CWS) on older drivers' head movements behavior at intersections was examined.Methods: Twenty-six old-adults, between 55 and 64 years of age, and 16 Older drivers between 65 and 83 years of age, participated in the study. A CWS (Mobileye Inc.) and a front-back in-vehicle camera (IVC) were installed in each of the participants' own vehicles for 6 months. The CWS was utilized to identify unsafe events during natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Automatic systems that assist drivers in their driving tasks seem to cause a behavioral adaptation that can unintentionally lead to danger [ 33 ]. There are only a few studies dealing specifically with ADAS [e.g., 6 , 34 ]. Shichrur et al [ 34 ] found that older drivers who use ADAS, which includes a collision warning system, drove many more hours and longer distances compared to driving habits prior to the use of the system.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Automatic systems that assist drivers in their driving tasks seem to cause a behavioral adaptation that can unintentionally lead to danger [ 33 ]. There are only a few studies dealing specifically with ADAS [e.g., 6 , 34 ]. Shichrur et al [ 34 ] found that older drivers who use ADAS, which includes a collision warning system, drove many more hours and longer distances compared to driving habits prior to the use of the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are only a few studies dealing specifically with ADAS [e.g., 6 , 34 ]. Shichrur et al [ 34 ] found that older drivers who use ADAS, which includes a collision warning system, drove many more hours and longer distances compared to driving habits prior to the use of the system. Yue et al [ 7 ]–using a Monte Carlo simulation based on predicted endogenous adoption of ADAS–found that the effectiveness of ADAS components could be almost 50% lower than the ideal effectiveness that had previously been proposed.…”
Section: Literature Reviewmentioning
confidence: 99%